Performance and Material-Dependent Holistic Representation of Unconscious Thought: A Functional Magnetic Resonance Imaging Study - Kageyama, Tetsuya; dos Santos Kawata, Kelssy Hitomi; Kawashima, Ryuta; Sugiura, Motoaki (Frontiers in Human Neuroscience, 2019)
Psychological research has shown the possibility that we can think unconsciously. Unconscious thought (UT) refers to cognitive or affective decision-related processes occurring outside conscious awareness. These are more effective in complex decision-making than conscious thought. Holistic representation plays a major role in UT and is characterized by a multimodal, value-related cognitive process. Recently, the neural correlates of UT were explored, but the findings did not confirm this hypothesis. In this study, we followed up this attempt using two UT tasks (person and consumer product evaluation) and improved the functional magnetic resonance imaging experimental protocol. Participants evaluated four alternatives with 12 attributes each. After the decision information was presented, in the UT condition, they completed a 1-back task for 120 s and evaluated each alternative and an independent 1-back task in the absence of any decision information. We conducted regression analysis of UT performance in both tasks. Results showed a positive correlation between UT performance and use of the anterior part of the precuneus/paracentral lobule in the person evaluation task and the posterior part of the precuneus, postcentral gyrus, middle occipital gyrus, and superior parietal lobule in the consumer product evaluation task. Overlapping precuneus use in both tasks indicated a multimodal, value-related cognitive process. These results were consistent with feature of holistic representation, supporting the central role of holistic representation in UT. The involvement of different subregions of the precuneus in two UT tasks may reflect the task dependency of the key representation critical for advantageous UT.